Patriarchy, Women, Land and Livelihoods on A1 farms in Zimbabwe. (December 2015) - Chiweshe, Manase Kudzai; Chakona, Loveness; Helliker, Kirk
In this article, we focus on patriarchy, women, land and livelihoods on A1 farms in Zimbabwe which arose from the fast track land reform programme. There is now significant literature on A1 farms in Zimbabwe. These studies include a number of ethnographic and comparative studies but this literature does not give sustained attention to patriarchy and women. In addition, though, a small number of works have appeared based upon a more focused gender analysis. We draw upon this more focused literature and offer fresh fieldwork evidence based on recent studies undertaken by two of the authors, in Goromonzi and Mazowe districts. At times, radical socio-spatial reorganisation such as fast track may destabilise systems of patriarchy. In the case of fast track, there has been a reconfiguration of relations between men and women yet this is uneven and contradictory and remains within the confines of patriarchal structures, practices and discourses. At the same time, women have manoeuvred and negotiated at local levels to enhance their lives and livelihoods.